2010
DOI: 10.1021/es101507s
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Partitioning Behavior of Polyfluorinated Iodine Alkanes in Environmental Matrices around a Fluorochemical Manufacturing Plant: Another Possible Source for Perfluorinated Carboxylic Acids?

Abstract: The indistinct origins of some ubiquitous perfluorinated alkyl acids have attracted great attention in recent decades. In this present work, even-chained polyfluorinated iodides (PFIs), a group of volatile perfluorinated compounds (PFCs), including four perfluorinated iodine alkanes (FIAs) and three polyfluorinated telomer iodides (FTIs) were confirmed to be present in the environment. A wide concentration range was found for FIAs at 1.41 to 3.08 × 10 4 pg/L, and for FTIs at 1.39 to 1.32 × 10 3 pg/L in the amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…Nevertheless, radio-isotopic labeling provides a means of overcoming this by measuring positron emission from radioactive decaying chemicals. Due to low natural abundance and lasting half-life, 14 C was selected to label PFAS precursors in order to trace chemical transformations in environmental and biological trials [10,11,26,42].…”
Section: C-labeling and Detection Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, radio-isotopic labeling provides a means of overcoming this by measuring positron emission from radioactive decaying chemicals. Due to low natural abundance and lasting half-life, 14 C was selected to label PFAS precursors in order to trace chemical transformations in environmental and biological trials [10,11,26,42].…”
Section: C-labeling and Detection Techniquesmentioning
confidence: 99%
“…Both fluorotelomer-based (FT) precursors (e.g., FTOHs and FTIs) and perfluoroalkane sulfonamido derivatives, including N-ethyl perfluorooctane sulfonamide (N-EtFOSA) and N-ethyl perfluorooctane sulfonamidoethanol (N-EtFOSE), were found in ambient air particles [13][14][15]. Fluorotelomer alcohols, monosubstituted and disubstituted PAPs, and perfluorooctane sulfonamidoacetic acid (FOSAA) analogues have frequently been detected in wastewater-treatment plant (WWTP) effluent, activated sludge and marine sediments [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, production of isopropyl PFOA using the telomerization process has also been reported (Kissa, 2005;Benskin et al, 2010a). Although telomerization has been widely used to produce APFO in Europe and North America in the period 2003e2015, its use in China has been fairly limited (Ruan et al, 2010;Fuxin, 2013;Wang et al, 2014a). Fluorotelomer products, some of which can degrade to PFCAs in the environment (Wallington et al, 2006;Wang et al, 2009;Butt et al, 2010), are however used in numerous consumer product applications including textile and paper treatment (Wang et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…8−10 PFIs have also been detected in the soil and atmosphere near an industrial facility that makes fluorinated chemicals in Shandong Province (northern China). 11,12 Production of perfluorooctyl iodide [PFOI ( Figure 1)] has increased in recent years because of its great commercial value. Studies have shown that the concentration of PFOI is relatively higher in the air and soil than the concentrations of the other derivatives of PFIs.…”
Section: ■ Introductionmentioning
confidence: 99%